Liquid optical cement, folding screen protective film and folding screen

By using a liquid optical glue composed of components A and B in the folding screen protective film, the problem of insufficient ball-and-brush resistance and pen-resistant performance in the prior art is solved, and high light transmittance, low haze and excellent adhesion properties are achieved, while reducing the thickness of the protective film and improving bending reliability.

CN119662198APending Publication Date: 2025-03-21PRIMA OPTICAL FILM (DONGGUAN) CO LTD +1

Patent Information

Application Number
CN202411946230.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing folding screen protective film has shortcomings in terms of ball-and-brush resistance and pen-resistance performance, and has high production and material costs, and poor bending reliability.

Method used

A liquid optical glue is used, which consists of component A and component B. Component A includes a catalyst and component B includes vinyl polyborosiloxane, hydrogen-containing crosslinking agent, end vinyl silicone rubber, vinyl silicone resin, tackifier and inhibitor. Through the combination of these components, the liquid optical glue has excellent anti-ball and anti-brush properties.

Benefits of technology

The high light transmittance, low haze and excellent adhesion properties of liquid optical glue are achieved, and it can combine excellent ball-fall resistance and brush-fall resistance, while reducing the thickness of the folding screen protective film and improving its bending reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005213715180000031
    Figure BDA0005213715180000031
  • Figure BDA0005213715180000051
    Figure BDA0005213715180000051
  • Figure BDA0005213715180000071
    Figure BDA0005213715180000071
Patent Text Reader

Abstract

The invention provides a liquid optical adhesive, a folding screen protective film and a folding screen, the liquid optical adhesive comprises a component A and a component B, the component A comprises a catalyst, and the component B comprises vinyl polyborosiloxane, a hydrogen-containing cross-linking agent, vinyl-terminated silicone rubber, vinyl silicone resin, a tackifier and an inhibitor; vinyl polyborosiloxane with specific parts is introduced into the component B to be matched with other components, so that the obtained liquid optical cement has a non-bovine characteristic, the cohesion strength of an adhesive film obtained after curing is remarkably improved, and then the liquid optical cement can have excellent ball falling resistance and pen falling resistance and is excellent in impact resistance; meanwhile, the film also has relatively high light transmittance, relatively low haze and excellent adhesion performance, is used for preparing the folding screen protection film, and can ensure that the obtained folding screen protection film can effectively protect a folding screen.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of display technology, and specifically relates to a liquid optical adhesive, a folding screen protective film and a folding screen. Background Art

[0002] With the continuous development of flexible OLED panel display technology, foldable screens have gradually entered the public eye. Foldable screens allow users to fold or unfold the screen, thereby meeting users' needs for different screen sizes, and can be folded into a folded state when not in use, making it easy for users to carry.

[0003] Since the folding screen uses a flexible OLED display panel, a protective film is needed to protect the screen. The protective film needs to have excellent scratch resistance and pen resistance to reduce the risk of poor display such as leakage and light spots in the flexible OLED panel.

[0004] There are two main technical solutions for existing foldable impact-resistant protective films. One is a four-layer structure, namely, from top to bottom, a transparent base film with a hardened layer added to the surface, an optical adhesive layer, an impact-resistant elastomer thermoplastic polyurethane (TPU) and an optical adhesive layer. The first optical adhesive layer bonds the transparent base film and TPU, and the second optical adhesive layer bonds the protective film to the transparent cover plate of the display screen. Although this type of protective film has good scratch resistance and a certain ability to protect the screen from impact, it has a large bending stress and requires two layers of optical adhesive for bonding, which increases the total thickness of the product, and is not friendly in terms of production cost, material cost and bending reliability. The other type is a three-layer structure, in which a layer of impact-resistant silicone is directly coated on the transparent base film with a hardened layer on the surface instead of TPU, and then connected to the transparent cover plate through an optical bonding layer. Compared with the first type of protective film, this type of protective film does not require an optical bonding layer between the transparent base film and the impact-resistant layer, which reduces the total thickness and saves production costs and material costs. However, it has very high requirements for impact-resistant silicone. It is difficult for impact-resistant silicone to have both interface adhesion and impact-resistant effects. The insufficient interface adhesion of impact-resistant silicone leads to white lines and debonding in the protective film during bending, and the impact-resistant effect of the impact-resistant silicone currently used in the protective glue is also poor.

[0005] For example, 202411196815.1 discloses a two-component impact-resistant optical adhesive and its preparation method and application. The two-component impact-resistant optical adhesive includes component A and component B, wherein component A includes specific portions of vinyl silicone resin and a catalyst, and component B includes specific portions of hydrogenated silicone resin, vinyl silicone rubber, a tackifier and an inhibitor, and the mass percentage of vinyl in the vinyl silicone resin is less than 2%; the optical adhesive obtained by the invention has low shear stress, high tensile strength, excellent impact energy absorption effect and high hardness; however, the optical adhesive provided by the invention does not record the anti-pencil drop ability, and the anti-ball drop ability still needs to be improved.

[0006] Therefore, developing a liquid optical adhesive with excellent anti-ball drop performance and anti-pen drop performance is still a technical problem that needs to be urgently solved in this field. Summary of the invention

[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a liquid optical adhesive, a folding screen protective film and a folding screen. The liquid optical adhesive has excellent anti-falling ball ability and pen-falling ability, and is also excellent in optical, mechanical and other indicators. It has high light transmittance, low haze and excellent adhesion performance. It is used to prepare a folding screen protective film, and can ensure that the obtained folding screen protective film effectively protects the folding screen.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a liquid optical adhesive, wherein the liquid optical adhesive comprises a component A and a component B;

[0010] The A component comprises the following components in parts by weight:

[0011] Catalyst 0.1-1 parts by weight;

[0012] The B component comprises the following components in parts by weight:

[0013]

[0014] Boron (B) is the fifth element, with 5 protons, 5 electrons, and an electronic configuration of 1S. 2 2S 2 2P 1 , and the outermost layer has 3 electrons, so the B element in the formed polyborosiloxane can react with 3 O - Form a shared electron pair, but because the electron pair of B is formed as unequal SP 3 Hybridization creates an empty P orbital, which can form a BO dynamic reversible weak bond with the lone pair of electrons on O;

[0015] Based on the above content, the inventors of the present invention found during the research process that polyborosiloxane has typical cold flow characteristics in the natural state, but when subjected to high strain rate impact, the weak bonds formed cannot be broken immediately, which increases the rigidity of the material, and this transformation form is reversible, so that the material has the property of shear thickening. Therefore, the liquid optical adhesive provided by the present invention creatively adds vinyl polyborosiloxane to component B, so that the resulting liquid optical adhesive can have excellent anti-dropping ability after film formation; in addition, the functional group carried by conventional polyborosiloxane is hydroxyl, which cannot participate in the cross-linking of the addition type formula, and exists in the colloid in the form of a plasticizer, which makes the colloid cohesive strength seriously insufficient. When the material encounters a sharp object (pen drop) instantaneous impact, the protection effect is not ideal. Therefore, the present invention also introduces vinyl into the structure of polyborosiloxane, and at the same time compounded with vinyl silicone resin, so that the cohesive strength of the adhesive film formed by the resulting liquid optical adhesive is improved, and the anti-pen drop force is further optimized.

[0016] In summary, the present invention introduces vinyl polyborosiloxane and vinyl silicone resin into component B to make the resulting liquid optical adhesive have non-Niu characteristics. The cohesive strength of the resulting adhesive film after curing is significantly improved, and it can have excellent anti-ball drop and anti-pencil drop properties. It also has high light transmittance, low haze and excellent adhesion properties. After curing, it has good adhesion to the base film and can be directly coated on the base film when used, thereby reducing the overall thickness of the folding screen protective film and improving its bending reliability. At the same time, the use of one optical bonding layer can be reduced. In addition, the liquid optical adhesive of the present invention maintains a high hardness, and the elastomer will not show white line phenomenon during daily use such as scratching and finger scratching, and the prepared protective adhesive can meet the bending reliability test.

[0017] The amount of the catalyst may be 0.1 parts by weight, 0.2 parts by weight, 0.4 parts by weight, 0.6 parts by weight, 0.8 parts by weight or 1 part by weight.

[0018] The amount of the vinyl polyborosiloxane can be 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 10 parts by weight, 12 parts by weight, 14 parts by weight or 16 parts by weight.

[0019] The amount of the hydrogen-containing crosslinking agent can be 0.8 parts by weight, 1 part by weight, 1.2 parts by weight, 1.4 parts by weight, 1.6 parts by weight, 1.8 parts by weight, etc.

[0020] The amount of the vinyl-terminated silicone rubber may be 30 parts by weight, 35 parts by weight, 40 parts by weight, 45 parts by weight, 50 parts by weight, 55 parts by weight or 60 parts by weight, etc.

[0021] The amount of the vinyl silicone resin can be 30 parts by weight, 32 parts by weight, 34 parts by weight, 36 parts by weight, 38 parts by weight, 40 parts by weight, 42 parts by weight, 44 parts by weight or 45 parts by weight, etc.

[0022] The amount of the tackifier can be 0.1 parts by weight, 0.2 parts by weight, 0.4 parts by weight, 0.6 parts by weight, 0.8 parts by weight, 1 part by weight, 1.2 parts by weight, 1.4 parts by weight, 1.6 parts by weight, 1.8 parts by weight or 2 parts by weight, etc.

[0023] The inhibitor may be used in an amount of 1 part by weight, 1.2 parts by weight, 1.4 parts by weight, 1.6 parts by weight, 1.8 parts by weight, 2 parts by weight, 2.2 parts by weight, 2.4 parts by weight, 2.6 parts by weight, 2.8 parts by weight or 3 parts by weight, etc.

[0024] Preferably, the catalyst comprises a platinum catalyst.

[0025] Preferably, the platinum catalyst includes any one of chloroplatinic acid, Karstedt platinum catalyst or Willing platinum catalyst, or a combination of at least two thereof.

[0026] Preferably, the platinum content in the platinum catalyst is 20 to 100 ppm, for example, 20 ppm, 30 ppm, 40 ppm, 50 ppm, 60 ppm, 70 ppm, 80 ppm, 90 ppm or 100 ppm.

[0027] Preferably, the structural formula of the vinyl polyborosiloxane is as follows:

[0028]

[0029] wherein m is an integer from 10 to 30, such as 10, 12, 14, 16, 18, 20, 22, 24, 26, 28 or 30; R1 is each independently selected from any one of C1 to C4 (e.g., C1, C2, C3, C4) straight chain or branched alkyl groups; R2 is each independently selected from any one of C2 to C6 (e.g., C1, C2, C3, C4, C5, C6) straight chain or branched olefin groups, and hydroxy groups, and at least one R2 is a C2 to C6 straight chain or branched olefin group.

[0030] Preferably, the boron content in the vinyl polyborosiloxane is 0.2-0.7 wt%, for example, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt% or 0.7 wt%.

[0031] Preferably, the vinyl content in the vinyl polyborosiloxane is 0.3-0.8wt%, for example, 0.3wt%, 0.32wt%, 0.34wt%, 0.36wt%, 0.38wt%, 0.4wt%, 0.42wt%, 0.44wt%, 0.46wt%, 0.48wt%, 0.5wt%, 0.6wt%, 0.7wt% or 0.8wt%, etc., and more preferably 0.3-0.5wt%.

[0032] In the present invention, there is no special restriction on the source of the vinyl polyborosiloxane, and the commercial product can be directly purchased, or it can be prepared according to the existing method. However, in order to ensure that the obtained liquid optical adhesive can have the best anti-pencil drop performance and anti-ball drop performance, the following method is preferably used for preparation:

[0033] (A) subjecting boric acid and terminal hydroxyl polysiloxane to an esterification reaction to obtain polyborosiloxane;

[0034] (B) Adding a vinyl end-capping agent to the obtained polyborosiloxane for reaction, the vinyl polyborosiloxane can be obtained.

[0035] Preferably, the temperature of the esterification reaction is 60-70°C, for example, 60°C, 62°C, 64°C, 66°C, 68°C or 70°C.

[0036] Preferably, the esterification reaction time is 3 to 4 h, for example, 3 h, 3.2 h, 3.4 h, 3.6 h, 3.8 h or 4 h.

[0037] Preferably, the boric acid in step (A) is added in the form of a boric acid solution, the boric acid solution uses a conventional solvent, such as methanol, and the mass ratio of the boric acid to the solvent is 1:(8-12).

[0038] Preferably, the reaction temperature in step (B) is 75-85°C, for example, 75°C, 77°C, 79°C, 81°C, 83°C or 85°C.

[0039] Preferably, the reaction time of step (B) is 2 to 4 h, for example 2 h, 2.5 h, 3 h, 3.5 h or 4 h.

[0040] Preferably, the preparation method of the vinyl polyborosiloxane specifically comprises the following steps:

[0041] a. mixing boric acid and a solvent to obtain a boric acid solution, and transferring the solution to a constant pressure funnel;

[0042] b. In a four-necked flask equipped with a thermometer, a stirrer, a condenser and a constant pressure funnel, weigh and add hydroxy-terminated polysiloxane, raise the temperature to 40-45°C, start dropping the boric acid solution, raise the temperature to 60-70°C after the addition is complete, and react for 3-4h to obtain polyborosiloxane;

[0043] c. Add vinyl end-capping agent into the four-necked flask, raise the temperature to 75-85°C, and react for 2-3h;

[0044] d. removing the solvent and by-products by distillation under reduced pressure to obtain a crude product of vinyl polyborosiloxane;

[0045] e. The crude vinyl polyborosiloxane product was dissolved in tetrachloromethane, the residual solid boric acid was removed by filtration, and the product was purified under reduced pressure at 25 to 35° C. to obtain a vinyl polyborosiloxane product.

[0046] Wherein, the terminal hydroxyl polysiloxane has the following structure:

[0047]

[0048] Wherein, R is independently selected from any one of C1-C4 (e.g., C1, C2, C3, C4) linear or branched alkyl groups, and n is an integer from 10 to 30 (e.g., 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, or 30, etc.).

[0049] Preferably, the hydroxyl content of the hydroxyl-terminated polysiloxane is 0.25-4.0wt%, for example, 0.25wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 3.7wt% or 4.0wt%.

[0050] Preferably, the viscosity of the terminal hydroxyl polysiloxane at 25° C. is 20 to 1000 mPa·s, for example, 20 mPa·s, 50 mPa·s, 100 mPa·s, 200 mPa·s, 400 mPa·s, 600 mPa·s, 800 mPa·s or 1000 mPa·s.

[0051] Preferably, the vinyl end-capping agent comprises tetramethyldivinyldisilazane and / or tetramethyldivinyldisiloxane.

[0052] Preferably, the mass percentage content of active hydrogen in the hydrogen-containing cross-linking agent is 0.1-1 wt%, for example, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt% or 1 wt%.

[0053] Preferably, the hydrogen-containing cross-linking agent includes hydrogen-containing silicone resin and / or hydrogen-containing silicone oil.

[0054] Preferably, the structural formula of the hydrogen-containing silicone resin is (H c R 1 3-c SiO 0.5 ) x (SiO2) y ;

[0055] Among them, R 1 Any one selected from C1-C10 (e.g., C1, C2, C4, C6, C8 or C10, etc.) straight chain or branched alkyl, C6-C10 (e.g., C6, C7, C8, C9 or C10, etc.) aryl, c is an integer of 1-3 (e.g., 1, 2 or 3), x and y are both positive integers, and the ratio of x to y is (1-1.4):1 (e.g., 1:1, 1.1:1, 1.2:1, 1.3:1 or 1.4:1, etc.).

[0056] Preferably, the weight average molecular weight of the hydrogen-containing silicone resin is 1000-5000, for example, 1000, 1500, 2000, 2500, 3000, 3500, 4000, 4500 or 5000.

[0057] Preferably, the structural formula of the hydrogen-containing silicone oil is as follows:

[0058]

[0059] Among them, R 2 Each independently selected from C1 to C10 (e.g., C1, C2, C4, C6, C8 or C10, etc.) straight or branched chain alkyl, hydrogen atom, R 3 Each is independently selected from any one of C1~C10 (for example, C1, C2, C4, C6, C8 or C10, etc.) straight chain or branched alkyl groups, w is an integer ≥0 (for example, 0, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10, etc.), and v is an integer >0 (for example, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10, etc.).

[0060] Preferably, the viscosity of the hydrogen-containing silicone oil at 25° C. is 20 to 100 mPa·s, for example, 20 mPa·s, 40 mPa·s, 60 mPa·s, 80 mPa·s or 100 mPa·s.

[0061] Preferably, the vinyl-terminated silicone rubber has the following structure:

[0062]

[0063] Wherein, R3 is selected from any one of C1~C5 (for example, C1, C2, C3, C4 or C5, etc.) straight chain or branched alkyl, C1~C5 (for example, C1, C2, C3, C4 or C5, etc.) alkoxy, R4 is vinyl, g is an integer of 4000~8000 (for example, 4000, 4200, 4400, 4600, 4800, 5000, 5200, 5400, 5600, 5800, 6000, 6500, 7000, 7500 or 8000, etc.), and h is an integer of 10~50 (for example, 10, 20, 30, 40 or 50, etc.).

[0064] Preferably, the relative molecular mass of the vinyl-terminated silicone rubber is 400,000 to 800,000, for example, 400,000, 450,000, 500,000, 550,000, 600,000, 650,000, 700,000, 750,000 or 800,000.

[0065] Preferably, the vinyl content in the vinyl-terminated silicone rubber is 0.01-0.25wt%, for example, 0.01wt%, 0.03wt%, 0.05wt%, 0.07wt%, 0.09wt%, 0.11wt%, 0.13wt%, 0.15wt%, 0.17wt%, 0.19wt%, 0.21wt%, 0.23wt% or 0.25wt%, etc., and more preferably 0.03-0.06wt%.

[0066] Preferably, the vinyl silicone resin includes any one of MQ vinyl silicone resin, MT vinyl silicone resin, MDT vinyl silicone resin or MTQ vinyl silicone resin, or a combination of at least two thereof, and more preferably MQ vinyl silicone resin.

[0067] Preferably, the M / Q ratio of the MQ vinyl silicone resin is 0.7 to 0.9, for example, 0.7, 0.72, 0.74, 0.76, 0.78, 0.8, 0.82, 0.84, 0.86, 0.88 or 0.9, etc.

[0068] Preferably, the vinyl content in the MQ vinyl silicone resin is ≤1.5wt%, for example, 1.5wt%, 1.3wt%, 1wt%, 0.9wt%, 0.8wt%, 0.7wt%, 0.6wt%, 0.5wt%, 0.4wt% or 0.3wt%, etc.

[0069] Preferably, the tackifier includes any one of an ester-containing organosilicon tackifier, an epoxy-containing organosilicon tackifier, a vinyl-containing siloxane tackifier or a boron-containing organosilicon tackifier, or a combination of at least two thereof.

[0070] Preferably, the inhibitor comprises any one of acetylenic alcohol compounds, vinyl ring compounds, polyvinyl silicone oils or maleate compounds, or a combination of at least two thereof.

[0071] Preferably, the alkynol compound includes 1-ethynyl-1-cyclohexanol.

[0072] Preferably, the liquid optical adhesive further includes 40 to 60 parts by weight (for example, 40 parts by weight, 42 parts by weight, 44 parts by weight, 46 parts by weight, 48 parts by weight, 50 parts by weight, 52 parts by weight, 54 parts by weight, 56 parts by weight, 58 parts by weight or 60 parts by weight, etc.) of a diluent.

[0073] In the present invention, the diluent may be partially added to component A and the rest to component B, or all of the diluent may be added to either component A or component B as required.

[0074] Preferably, the diluent includes any one of petroleum ether, white spirit, toluene, n-heptane, ethyl acetate or cyclohexane, or a combination of at least two thereof.

[0075] When the liquid optical adhesive provided by the present invention is used, the substances in component B are first mixed evenly, and then mixed with component A and then directly coated.

[0076] In a second aspect, the present invention provides a folding screen protective film, the folding screen protective film comprising a hardening layer, a base film, an optical adhesive layer, an adhesive layer and a first release film stacked from top to bottom;

[0077] The optical adhesive layer is obtained by curing the liquid optical adhesive as described in the first aspect.

[0078] The liquid optical adhesive provided in the first aspect of the present invention has strong adhesion to the base film and can be directly coated on the surface of the base film without adding an adhesive layer between the optical adhesive layer and the base film, thereby effectively reducing the thickness of the resulting folding screen protective film, so that the resulting folding screen protective film has good bending reliability while also having good anti-ball drop capability and anti-pen drop capability.

[0079] Preferably, the material of the hardening layer includes acrylic resin.

[0080] Preferably, the thickness of the hardened layer is 2-10 μm, for example, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.

[0081] Preferably, the base film includes any one of a PET film, a PP film, a PVC film or a TPU film.

[0082] Preferably, the thickness of the optical adhesive layer is 30-50 μm, for example, 30 μm, 32 μm, 34 μm, 36 μm, 38 μm, 40 μm, 42 μm, 44 μm, 46 μm, 48 μm or 50 μm.

[0083] Preferably, the adhesive layer includes an organic silicone OCA adhesive layer or an acrylic OCA adhesive layer.

[0084] Preferably, the thickness of the adhesive layer is 20-200 μm, for example, 20 μm, 40 μm, 60 μm, 80 μm, 100 μm, 120 μm, 140 μm, 160 μm, 180 μm or 200 μm.

[0085] Preferably, a second release film is also included on the surface of the hardened layer on the side away from the base film; the first release film and the second release film both protect the folding screen protective film during the manufacturing process and transportation, and the first release film and the second release film will be removed when in use.

[0086] Preferably, the curing conditions are: first heating at 80-90°C (e.g., 80°C, 82°C, 84°C, 86°C, 88°C or 90°C, etc.) for 2-5 min (e.g., 2 min, 2.5 min, 3 min, 3.5 min, 4 min, 4.5 min or 5 min, etc.), and then heating at 90-100°C (e.g., 90°C, 92°C, 94°C, 96°C, 98°C or 100°C, etc.) for 2-5 min (e.g., 2 min, 2.5 min, 3 min, 3.5 min, 4 min, 4.5 min or 5 min, etc.). min, etc.), then heated at 110-120°C (e.g., 110°C, 112°C, 114°C, 116°C, 118°C or 120°C, etc.) for 2-5min (e.g., 2min, 2.5min, 3min, 3.5min, 4min, 4.5min or 5min, etc.), and finally ripened at 60-65°C (e.g., 60°C, 61°C, 62°C, 63°C, 64°C or 65°C, etc.) for 18-24h (e.g., 18h, 19h, 20h, 21h, 22h, 23h or 24h, etc.) to complete the curing.

[0087] In a third aspect, the present invention provides a method for preparing the folding screen protective film according to the second aspect, the preparation method comprising the following steps:

[0088] A hardening layer material is coated on one surface of the base film to form a hardened layer after curing; the liquid optical adhesive as described in the first aspect is coated on the other surface of the base film to obtain a laminate after curing; an adhesive layer is superimposed on one surface of the optical adhesive layer of the obtained laminate, and the other surface of the adhesive layer is covered with a first release film to obtain the folding screen protective film.

[0089] Preferably, after forming the hardened layer, the method further includes laminating a second release film on a surface of the hardened layer away from the base film.

[0090] In a third aspect, the present invention provides a folding screen, which includes a screen body and a folding screen protective film as described in the second aspect and arranged on a surface of one side of the screen body.

[0091] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0092] Compared with the prior art, the present invention has the following beneficial effects:

[0093] (1) The liquid optical adhesive provided by the present invention comprises a component A and a component B, wherein the component A comprises a catalyst, and the component B comprises vinyl polyborosiloxane, a hydrogen-containing crosslinking agent, a vinyl-terminated silicone rubber, a vinyl silicone resin, a tackifier and an inhibitor; by introducing a specific amount of vinyl polyborosiloxane into the component B and matching it with other components, the obtained liquid optical adhesive has non-coated characteristics, and the cohesive strength of the obtained adhesive film after curing is significantly improved, thereby being able to have excellent anti-ball drop and anti-pencil drop properties, excellent impact resistance, and at the same time having high light transmittance, low haze and excellent adhesion performance, and is used to prepare a folding screen protective film, which can ensure that the obtained folding screen protective film effectively protects the folding screen.

[0094] (2) Specifically, the optical indicators of the liquid optical adhesive provided by the present invention are transmittance>90%, haze<1.0%, and yellowing<1.0, which have excellent performance and can meet the indicators used in optical displays; and the storage modulus is as high as 60Kpa, 50% linear deformation stress<45Kpa, tensile strength can reach above 1.2Mpa, and elongation at break>1000%, so that the material meets the bending reliability test>200,000 times, R=1.5; at the same time, the PET adhesive does not debond under the 100-grid test, and has good adhesion to the base film after curing. When used, it can be directly coated on the base film to reduce the thickness. The material maintains a high hardness of 10A, and the elastomer will not show white lines when scratched or scratched in daily use. DETAILED DESCRIPTION

[0095] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0096] Synthesis example 1

[0097] This synthesis example provides a vinyl polyborosiloxane A1, the boron content is 0.5wt%, the vinyl content is 0.5wt%, and the specific structural formula is as follows:

[0098]

[0099] Wherein, m=12, R1 is methyl, and R2 is hydroxyl or vinyl;

[0100] The preparation method of vinyl polyborosiloxane A1 provided in this synthesis example comprises the following steps:

[0101] a. Boric acid (H3BO3 analytical grade) and methanol (reagent grade) were mixed in a mass ratio of 1:10 to obtain a boric acid solution, and transferred to a constant pressure dropping funnel;

[0102] b. 370 g of hydroxy-terminated polydimethylsiloxane (hydroxyl content of 3.78 wt %, viscosity of 35 mPa·s / 25°C, supplier: Keqi Polymer Materials Research Institute Co., Ltd., model JS0001) was weighed and added into a four-necked flask, and the boric acid solution was connected to one of the four-necked flasks, and the other three flasks were sealed with glass stoppers;

[0103] c. The four-necked flask was heated to 45°C and 144.87 g of boric acid solution was added dropwise. After the addition was completed, the temperature was raised to 60°C and the reaction was carried out for 4 hours to obtain polyborosiloxane;

[0104] d. Add 5.08 g of tetramethyldivinyldisilazane into a four-necked flask, raise the temperature to 80°C, and react for 3 hours;

[0105] e..using reduced pressure distillation at 100°C to remove the methanol diluent and by-products to obtain a crude vinyl polyborosiloxane product;

[0106] f. The crude vinyl polyborosiloxane product was dissolved in tetrachloromethane, the residual solid boric acid was removed by filtration, and purified under reduced pressure at 30° C. to obtain the vinyl polyborosiloxane product A1.

[0107] Synthesis example 2

[0108] This synthesis example provides a vinyl polyborosiloxane A2, with a boron content of 0.5wt%, a vinyl content of 1.0wt%, and a structural formula as follows:

[0109]

[0110] Wherein, m=12, R1 is methyl, and R2 is hydroxyl or vinyl;

[0111] The preparation method of vinyl polyborosiloxane A2 provided in this synthesis example comprises the following steps:

[0112] a. Boric acid (H3BO3 analytical grade) and methanol (reagent grade) were mixed in a mass ratio of 1:10 to obtain a boric acid solution, and transferred to a constant pressure dropping funnel;

[0113] b. 370 g of hydroxy-terminated polydimethylsiloxane (hydroxyl content of 3.78 wt %, viscosity of 35 mPa·s / 25°C, supplier: Keqi Polymer Materials Research Institute Co., Ltd., model JS0001) was weighed and added into a four-necked flask, and the boric acid solution was connected to one of the four-necked flasks, and the other three flasks were sealed with glass stoppers;

[0114] c. The four-necked flask was heated to 45°C and 144.87 g of boric acid solution was added dropwise. After the addition was completed, the temperature was raised to 60°C and the reaction was carried out for 4 hours to obtain polyborosiloxane;

[0115] d. Add 13.71 g of tetramethyldivinyldisilazane into a four-necked flask, raise the temperature to 80°C, and react for 3 hours;

[0116] e..using reduced pressure distillation at 100°C to remove the methanol diluent and by-products to obtain a crude vinyl polyborosiloxane product;

[0117] f. The crude vinyl polyborosiloxane product was dissolved in tetrachloromethane, the residual solid boric acid was removed by filtration, and purified under reduced pressure at 30° C. to obtain a vinyl polyborosiloxane product A2.

[0118] Comparative Synthesis Example 1

[0119] This comparative synthesis example provides a polyborosiloxane D1, the boron content is 0.5wt%;

[0120] The preparation method of polyborosiloxane D1 provided in this comparative synthesis example comprises the following steps:

[0121] a. Boric acid (H3BO3 analytical grade) and methanol (reagent grade) were mixed in a mass ratio of 1:10 to obtain a boric acid solution, and transferred to a constant pressure dropping funnel;

[0122] b. 370 g of hydroxy-terminated polydimethylsiloxane (hydroxyl content of 3.78 wt %, viscosity of 35 mPa·s / 25°C, supplier: Keqi Polymer Materials Research Institute Co., Ltd., model JS0001) was weighed and added into a four-necked flask, and the boric acid solution was connected to one caliber of the flask, and the other three calibers were sealed with glass stoppers;

[0123] c. Heat the four-necked flask to 45°C and begin to dropwise add 144.87 g of boric acid solution. After the addition is complete, heat to 60°C and react for 4 hours;

[0124] d..using reduced pressure distillation at 100°C to remove the methanol diluent and by-products to obtain a crude polyborosiloxane product;

[0125] f. The crude polyborosiloxane was dissolved in tetrachloromethane, the residual solid boric acid was removed by filtration, and the mixture was purified under reduced pressure at 30° C. to obtain the polyborosiloxane D1.

[0126] The materials and grades involved in the following examples and comparative examples are as follows:

[0127] (A) Platinum catalyst: purchased from Delta Silicone, model number YF100515, liquid, platinum content of 20 ppm.

[0128] (B1) Vinyl polyborosiloxane A1: from Synthesis Example 1, high viscosity cake;

[0129] Vinyl polyborosiloxane A2: from Synthesis Example 2, high viscosity cake-like.

[0130] (B2) Hydrogen-containing crosslinking agent: purchased from Shandong Dayi Chemical Industry, active hydrogen content is 0.3-0.6 wt %, liquid, specifically methyl hydrogen-containing MQ resin.

[0131] (B3) Vinyl-terminated silicone rubber: purchased from Dongguan Dongjue Trading Co., Ltd., with a vinyl mass percentage of 0.03-0.06 wt%, liquid, and brand number 110-8S.

[0132] (B4) Vinyl silicone resin A: purchased from Jiangsu Keqi Polymer Materials Research Institute Co., Ltd., with a vinyl content of 0.5-1 wt%, powder, specifically methyl vinyl MQ resin, brand VMQ-1005;

[0133] Vinyl silicone resin B: purchased from Jiangsu Keqi Polymer Material Research Institute Co., Ltd., with a vinyl content of 1.15 wt %, powder, specifically methyl vinyl MQ resin, brand CF-910.

[0134] (B5) Thickener: purchased from Guangzhou Shuangtao Fine Chemical Co., Ltd., in liquid form, specifically a vinyl-containing siloxane thickener with a brand name of DP-231.

[0135] (B6) Inhibitor: purchased from Sane Chemical Technology (Shanghai) Co., Ltd., liquid, purity 100%, specifically 1-ethynyl-1-cyclohexanol, brand number D080035.

[0136] (B7) Xylene: purchased from Dongguan Zhouyang Trading Co., Ltd., liquid, industrial grade.

[0137] (D1) Polyborosiloxane D1: from Comparative Synthesis Example 1.

[0138] Examples 1 to 7 and Comparative Examples 1 to 4

[0139] Examples 1 to 7 and Comparative Examples 1 to 4 respectively provide a liquid optical adhesive, which includes a component A and a component B, and the components included in the component A and the component B are shown in Table 1;

[0140] In Table 1, the dosage units of each component are all "parts by weight";

[0141] Table 1

[0142]

[0143] Table 2

[0144]

[0145] The preparation methods of the liquid optical adhesive provided in Examples 1 to 7 and Comparative Examples 1 to 4 include the preparation of component A and the preparation of component B:

[0146] The preparation of the A component comprises: weighing a platinum-type catalyst and setting it aside;

[0147] The preparation method of the B component comprises: weighing vinyl polyborosiloxane, hydrogen-containing crosslinking agent, vinyl-terminated silicone rubber, vinyl silicone resin, tackifier, inhibitor and diluent according to proportion, stirring at a speed of 100 rpm for 30 minutes, filtering, and obtaining the B component;

[0148] Just mix component A and component B before use.

[0149] Performance Test:

[0150] (1) First, a folding screen protective film is prepared, specifically including: coating an acrylic hardening layer (5 μm) on the surface of a PET base film, and laminating a release film on the surface of the acrylic hardening layer; after coating the other surface of the PET base film with liquid optical adhesive, first heating at 85°C for 2 min, then heating at 100°C for 2 min, then heating at 120°C for 2 min, and aging at 60°C for 24 h, an optical adhesive layer (45 μm) is formed to obtain a laminate; an organic silicon OCA adhesive layer (35 μm, Nitto brand FL-09) is superimposed on the surface of the optical adhesive layer of the obtained laminate, and finally a release film is covered on the surface of the organic silicon OCA adhesive layer to obtain the folding screen protective adhesive. Then, the release film of the obtained folding screen protective film is torn off to expose the surface of the organic silicon OCA adhesive layer, and the folding screen protective film is bonded to the folding screen surface by roller bonding, and the release film on the other surface is torn off, and then the drop ball absorption rate, drop ball height, pen drop height and bending reliability are tested, and the specific test method is as follows:

[0151] ① Drop ball absorption rate: Place the protective film on the test platform of the foam impact performance tester, and let a 10g steel ball fall freely from a height of 75cm onto the liquid optical adhesive film. Compare it with the PET film that has only been hardened, and calculate the drop ball absorption rate;

[0152] ② Drop height: Let a 32.15g stainless steel ball fall freely from different heights onto the folding screen with the folding screen protective film attached, and record the height until broken points and bright points appear.

[0153] ③ Pen drop height: Drop the tip of a 20g stainless steel contoured ballpoint pen from different heights onto the folding screen attached to the folding screen protective film, and record the height until broken points and bright points appear.

[0154] ③ Bending reliability: The folding display screen with a folding screen protective film is fixed on a dynamic bending machine with a folding curvature of 1.5mm. After folding 200,000 times at room temperature, the state of the protective film is observed. If there is no appearance defect, it is OK. If there are white lines, delamination, delamination and other appearance abnormalities, it is NG.

[0155] (2) Light transmittance: The light transmittance of the folding screen protective film is tested in accordance with the method for determination of light transmittance and haze of transparent plastics in GB / T 2410-2008.

[0156] The liquid optical adhesives provided in Examples 1 to 7 and Comparative Examples 1 to 4 were tested according to the above test method. The test results are shown in Table 3:

[0157] Table 3

[0158] Drop ball absorption rate / % Drop ball height / cm Pen height / cm Bending reliability Light transmittance / % Example 1 81 5.6 3.3 OK 91.2 Example 2 75 5 3.5 OK 91.1 Example 3 86 6 3.0 OK 90.8 Example 4 78 5.6 3.0 OK 90.5 Example 5 76 5.4 3.6 OK 90.5 Example 6 74 5 2.8 OK 90.6 Example 7 71 4.8 3.0 OK 90.1 Comparative Example 1 76 5.0 2.6 OK 90.2 Comparative Example 2 68 4.8 2.9 OK 90.2 Comparative Example 3 83 5.8 2.3 NG 90.1 Comparative Example 4 73 5.1 2.6 NG 90.1

[0159] From the data in Table 3, we can see that:

[0160] The folding screen protective film provided in Examples 1 to 5 has a light transmittance of 90.5 to 91.2%, a ball drop absorption rate of up to 75 to 81%, a ball drop height of 5 to 6 cm, a pen drop height of 3.0 to 3.6 cm, and the bending reliability test is OK, with excellent ball drop performance, pen drop performance and bending reliability.

[0161] By comparing Example 1 and Comparative Example 1, it can be seen that the use of polyborosiloxane to replace vinyl polyborosiloxane will lead to a decrease in the drop ball absorption rate, pen drop height and ball drop height of the obtained folding screen protective film, and the light transmittance is also reduced.

[0162] By comparing Example 1 with Comparative Examples 2 to 3, it can be seen that if the dosage of vinyl polyborosiloxane is too low, the ball drop absorption rate, pen drop height and ball drop height of the obtained folding screen protective film will also decrease, while if the dosage of vinyl polyborosiloxane is too low, the bending reliability of the obtained folding screen protective film will directly be NG.

[0163] Comparing Example 1 with Comparative Example 4, it can be seen that if the amount of hydrogen-containing cross-linking agent is too high, the bending reliability of the obtained folding screen protective film will be directly NG.

[0164] Finally, by comparing Example 1 with Examples 6 to 7, it can be seen that too high a vinyl content in vinyl polyborosiloxane and too high a vinyl content in vinyl silicone resin will also lead to a decrease in the impact resistance of the resulting folding screen protective film.

[0165] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A liquid optical adhesive, characterized in that: The liquid optical adhesive comprises component A and component B; The A component comprises the following components in parts by weight: Catalyst 0.1-1 parts by weight; The B component comprises the following components in parts by weight:

2. The liquid optical adhesive according to claim 1, characterized in that: The catalyst comprises a platinum catalyst; Preferably, the platinum catalyst comprises any one or a combination of at least two of chloroplatinic acid, Karstedt platinum catalyst or Willing platinum catalyst; Preferably, the platinum content in the platinum catalyst is 20-100 ppm.

3. The liquid optical adhesive according to claim 1 or 2, characterized in that: The structural formula of the vinyl polyborosiloxane is as follows: wherein m is an integer of 10 to 30, R1 is independently selected from any one of C1 to C4 straight chain or branched chain alkyl groups, R2 is independently selected from any one of C2 to C6 straight chain or branched chain olefin groups and hydroxy groups, and at least one R2 is a C2 to C6 straight chain or branched chain olefin group; Preferably, the boron content in the vinyl polyborosiloxane is 0.2 to 0.7 wt %; Preferably, the vinyl content in the vinyl polyborosiloxane is 0.3 to 0.8 wt %, more preferably 0.3 to 0.5 wt %.

4. The liquid optical adhesive according to any one of claims 1 to 3, characterized in that: The content of active hydrogen in the hydrogen-containing crosslinking agent is 0.1 to 1 wt%; Preferably, the hydrogen-containing cross-linking agent comprises hydrogen-containing silicone resin and / or hydrogen-containing silicone oil; Preferably, the structural formula of the hydrogen-containing silicone resin is (H c R 1 3-c SiO 0.5 ) x (SiO2) y , Among them, R 1 Any one selected from C1-C10 straight chain or branched alkyl, C6-C10 aryl, c is an integer of 1-3, x and y are both positive integers, and the ratio of x to y is (1-1.4):1; Preferably, the weight average molecular weight of the hydrogen-containing silicone resin is 1000 to 5000; Preferably, the structural formula of the hydrogen-containing silicone oil is as follows: Among them, R 2 Each independently selected from any one of a C1-C10 straight chain or branched alkyl group and a hydrogen atom, R 3 Each is independently selected from any one of C1-C10 straight chain or branched alkyl groups, w is an integer ≥ 0, and v is an integer > 0; Preferably, the viscosity of the hydrogen-containing silicone oil at 25° C. is 20 to 100 mPa·s.

5. The liquid optical adhesive according to any one of claims 1 to 4, characterized in that: The vinyl-terminated silicone rubber has the following structure: Wherein, R3 is selected from any one of C1-C5 straight chain or branched alkyl and C1-C5 alkoxy, R4 is vinyl, g is an integer of 4000-8000, and h is an integer of 10-50; Preferably, the relative molecular mass of the vinyl-terminated silicone rubber is 400,000 to 800,000; Preferably, the vinyl content in the vinyl-terminated silicone rubber is 0.01 to 0.25 wt %, and more preferably 0.03 to 0.06 wt %; Preferably, the vinyl silicone resin includes any one of MQ vinyl silicone resin, MT vinyl silicone resin, MDT vinyl silicone resin or MTQ vinyl silicone resin, or a combination of at least two thereof, and more preferably MQ vinyl silicone resin; Preferably, the M / Q ratio of the MQ vinyl silicone resin is 0.7 to 0.9; Preferably, the vinyl content in the MQ vinyl silicone resin is ≤1.5wt%, more preferably ≤1wt%.

6. The liquid optical adhesive according to any one of claims 1 to 5, characterized in that: The tackifier includes any one or a combination of at least two of an ester-containing organosilicon tackifier, an epoxy-containing organosilicon tackifier, a vinyl-containing siloxane tackifier or a boron-containing organosilicon tackifier; Preferably, the inhibitor comprises any one or a combination of at least two of acetylenic alcohol compounds, vinyl ring compounds, polyvinyl silicone oils or maleate compounds; Preferably, the acetylenic alcohol compound comprises 1-ethynyl-1-cyclohexanol; Preferably, the liquid optical adhesive further comprises 40 to 60 parts by weight of a diluent; Preferably, the diluent includes any one of petroleum ether, white spirit, toluene, n-heptane, ethyl acetate or cyclohexane, or a combination of at least two thereof.

7. A folding screen protective film, characterized in that: The folding screen protective film includes a hardening layer, a base film, an optical adhesive layer, an adhesive layer and a first release film stacked from top to bottom; The optical adhesive layer is obtained by curing the liquid optical adhesive as claimed in any one of claims 1 to 6.

8. The folding screen protective film according to claim 7, characterized in that: The material of the hardened layer includes acrylic resin; Preferably, the thickness of the hardened layer is 2 to 10 μm; Preferably, the thickness of the optical adhesive layer is 30-50 μm; Preferably, the adhesive layer comprises an organic silicon OCA adhesive layer or an acrylic OCA adhesive layer; Preferably, the thickness of the adhesive layer is 20 to 200 μm; Preferably, a second release film is further provided on a surface of the hardened layer away from the base film; Preferably, the curing conditions are: first heating at 80-90°C for 2-5 min, then heating at 90-100°C for 2-5 min, then heating at 110-120°C for 2-5 min, and finally aging at 60-65°C for 18-24 h to complete the curing.

9. A method for preparing a folding screen protective film as claimed in claim 7 or 8, characterized in that: The preparation method comprises the following steps: A hardening layer material is coated on one surface of the base film, and a hardened layer is formed after curing; the liquid optical adhesive as claimed in any one of claims 1 to 6 is coated on the other surface of the base film, and a laminate is obtained after curing; an adhesive layer is superimposed on one surface of the optical adhesive layer of the obtained laminate, and a first release film is covered on the other surface of the adhesive layer to obtain the folding screen protective film; Preferably, after forming the hardened layer, the method further includes laminating a second release film on a surface of the hardened layer away from the base film.

10. A folding screen, characterized in that: The folding screen includes a screen body and a folding screen protective film as described in claim 7 or 8, which is arranged on a surface of one side of the screen body.

Citation Information

Patent Citations

  • Two-component impact-resistant optical cement as well as preparation method and application thereof

    CN118956331A

Cited By

  • Boron-containing addition type curing modified organic silicon LED packaging agent and preparation method thereof

    CN120442059A